Cobalt-based catalyst for ammonia synthesis under ambient conditions via transient confinement - Keran Lv; Mengqian Xu; Li Yang; Chenghu Wei; Jikai Sun; Xu Fang; Tie Yu; Zhenyu Li; Weiqiao Deng (Nature Communications)
Abstract The Haber-Bosch process is used for industrial ammonia production worldwide, and it accounts for ~2% of the global energy consumption and 1.3% anthropogenic carbon footprint. Ammonia synthesis under ambient conditions with minimum carbon emission is highly desired, but it is still in the initial stage. Herein, we report a cobalt-based catalyst for ammonia continuous synthesis under ambient conditions via mechanochemistry. To describe mechanochemistry of ammonia synthesis, density functional theory (DFT) calculation was carried out and a transient confinement was discovered. 5 dual side models with Fe, Co, Ni, Cu, Ag have been set up and the Co dual side model exhibits the highest transient confinement effect with the maximum energy barrier reducing from 1.3 eV to 0.62 eV. The experiment confirmed cobalt powders in mechanochemical synthesis of ammonia showed the highest catalytic activity. By using the Co catalyst, up to 13.7 μmol·gcat −1·h−1 ammonia has been achieved under ambient conditions, and the cobalt-based catalyst can maintain its activity more than 350 h without deactivation. This represents the longest lifespan for ammonia synthesis among all the various methods reported under room temperature and atmospheric pressure to the best of our knowledge, which is also 10 times longer than the recent reported FeCs catalysts via mechanocatalysis under ambient conditions. This study suggests that continuous mechano-synthesis of ammonia under ambient condition is valuable.